Syllidae (Annelida: Phyllodocida) from the deep Mediterranean Sea, with the description of three new species - Langeneck, Joachim; Musco, Luigi; Busoni, Giulio; Conese, Ilaria; Aliani, Stefano; Castelli, Alberto (Zootaxa, 2018)
Despite almost two centuries of research, the diversity of Mediterranean deep-sea environments remain still largely unexplored. This is particularly true for the polychaete family Syllidae. We report herein 14 species; among them, we describe Erinaceusyllis barbarae n. sp., Exogone sophiae n. sp. and Prosphaerosyllis danovaroi n. sp. and report Parexogone wolfi San Martín, 1991, Exogone lopezi San Martín, Ceberio & Aguirrezabalaga, 1996 and Anguillosyllis Day, 1963 for the first time from the Western Mediterranean, the latter based on a single individual likely belonging to an undescribed species. Moreover, we re-establish Syllis profunda Cognetti, 1955 based on type and new material. Present data, along with a critical analysis of available literature, show that Syllidae are highly diverse in deep Mediterranean environments, even though they are rarely reported, probably due to the scarce number of studies devoted to the size-fraction of benthos including deep-sea syllids. Most deep-sea Syllidae have wide distributions, which do not include shallow-waters. 100 m depth apparently represents the boundary between the assemblages dominated by generalist shallow water syllids like Exogone naidina Ørsted, 1843 and Syllis parapari San Martín & López, 2000, and those deep-water assemblages characterised by strictly deep-water species like Parexogone campoyi San Martín, Ceberio & Aguirrezabalaga, 1996, Parexogone wolfi San Martín, 1991 and Syllis sp. 1 (= Langerhansia caeca Katzmann, 1973).